An Annotated Checklist of Newly Recorded Macromoth Species (Lepidoptera: Heterocera) with Host Plant Records from Peninsular Malaysia - Badrud’din, Sofwan; Barlow, Henry S.; Fadil, Khalid (Zootaxa, 2026)
Numerous studies on moth diversity have been conducted in Borneo, Sumatra, and Thailand. However, research on species richness and distribution in the neighbouring region of Peninsular Malaysia remains relatively limited. This paper analyses two collections, primarily of macromoths collected (i) in the late 1960s to early 1970s by the late H F O’B Traill at Batang Berjuntai, Selangor and (ii) by H S Barlow as well as latterly by Sofwan Badrud’din and Khalid Fadil at Genting Tea Estate (GTE), Genting Sempah, Pahang, from 1971 to date. Comprehensive identification of 3,492 species from the GTE collection has produced many range extensions of moths previously not recorded from Peninsular Malaysia. In total, 309 species are new records for Peninsular Malaysia within 9 families; Erebidae (140), Geometridea (60), Nolidae (52), Noctuidae (22), Euteliidae (15), Drepanidae (6), Uraniidae (7), Notodontidae (5), Zygaenidae (2). Of these, 97 species are illustrated with some showcasing sexual dimorphism. Additionally, the genitalia and other structures of 17 selected species were illustrated, with several described in detail for the first time. Numerous morphospecies are excluded from this study’s checklist due to their overwhelming numbers with estimation of 427 species.